Ion microbeam formation for study of radiationinduced segregation at grain boundaries in construction materials - Romanenko, A.V.; Ponomarov, A.A.; Ponomarev, A.G. (Вопросы атомной науки и техники, 2015)
The approaches for creating focused ion beams with a high current density and near-uniform current distribution in a spot, that allows an uniform dose for further micro irradiation technique, were considered. A numerical simulation of the microbeam formation was performed taking into account the effect of nonuniform distribution of the ion beam. The calculation method for a deconvolution of the beam brightness distribution parameters was improved. Experiments to verify theoretical calculations were performed.